(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article examines how reading literature enhances English writing skills through vocabulary enrichment, stylistic development, and grammatical proficiency. Synthesizing existing research, it highlights literature’s role in fostering critical thinking, cultural awareness, and writing motivation. Key findings reveal that consistent literary exposure expands learners’ lexical range, models complex syntax, and encourages sophisticated stylistic choices. Additionally, analytical engagement with texts cultivates originality and depth in writing, while cultural narratives improve contextual relevance. The study emphasizes integrating literature into language curricula to maximize writing development and calls for further research on pedagogical strategies and quantitative outcomes.